(untitled) (International journal of medical sciences, 2026)
The intestinal microbiota is recognized as an important regulator of metabolism in the human body. The metabolites it produces - short-chain fatty acids (SCFA), signaling molecules that activate incretin secretion, and neuroactive substances - regulate energy metabolism, insulin sensitivity, and central nervous system function. Disruption of the microbiota composition leads to a weakening of the intestinal barrier function, the development of low-grade chronic inflammation, and insulin resistance. This article analyzes the main molecular mechanisms of microbiota's influence on metabolism.